1997
DOI: 10.1093/oxfordjournals.aje.a009226
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Aspects of Recalling and Reporting Health-related Events: Papanicolaou Smears, Clinical Breast Examinations, and Mammograms

Abstract: This paper reports an examination of cognitive processes used by 178 women aged 50 years and older in retrieving information about the frequency with which they received Papanicolaou smears, mammograms, and clinical breast examinations. Women were selected from a health maintenance organization in which they had been enrolled for at least 5 1/2 years. The literature suggested that reporting of regular events such as these kinds of tests is likely to be based on schemas, which is an estimation technique in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 36 publications
2
71
0
Order By: Relevance
“…For subjects who had an endoscopy, multiple physicians may have been involved in the process (e.g., primary care physician made the referral, whereas gastroenterologist conducted the procedure); however, we sought validation from only one physician. The overreporting of all three tests that was observed in our study is generally supported by the literature (1,2,(4)(5)(6)11).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For subjects who had an endoscopy, multiple physicians may have been involved in the process (e.g., primary care physician made the referral, whereas gastroenterologist conducted the procedure); however, we sought validation from only one physician. The overreporting of all three tests that was observed in our study is generally supported by the literature (1,2,(4)(5)(6)11).…”
Section: Discussionsupporting
confidence: 92%
“…However, prior research has found that self-report of cancer screening may be inaccurate and prone to biases (1,2). Therefore, validation of self-reports through medical chart audit has long been viewed as the ''gold standard'' for assessing the veracity of self-reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have assessed the accuracy of selfreporting of cervical screening attendance, [5][6][7][8][9][10][11][12][13][14][15][16] but the available data on the accuracy of self-reporting of the occurrence of smear abnormalities are limited. 17,18 Studies examining the accuracy of the self-reporting of screening attendance have consistently found it to be a sensitive method of assessment, but it has a low specificity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…62 The highest rates of over-reporting were found among studies conducted in county health departments and public health clinics, and with ethnic populations. Possible reasons for over-reporting include: respondents' use of schemas (eg, associating behavior with a pattern of events such as a regular check-up) 67 and cultural differences. 68 Recent studies have called into question the completeness of medical records in certain settings.…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%